2020
DOI: 10.1063/5.0019349
|View full text |Cite
|
Sign up to set email alerts
|

Lateral and vertical growth of Mg-doped GaN on trench-patterned GaN films

Abstract: Growth of Mg-doped GaN on trench-patterned GaN films consists of competing lateral and vertical growth fronts that result in regions with different electronic properties. Under typical growth conditions, lateral growth from the trench sidewall occurs at a faster rate than vertical growth from the trench base. When the trench width is sufficiently narrow, the growth fronts from opposite sidewalls coalesce and lead to eventual planarization of the top surface. Secondary electron imaging and cathodoluminescence m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The starting regrowth interface is slightly displaced from the initial trench edge due to mass transport via sublimation and condensation of Ga during temperature ramp-up and annealing (Figure e). , The terminal growth surface was observed in cross-section by cleaving along a [12̅10] axis ( a -axis), exposing the (101̅0) ( m -plane) surface (Figure f). The UID-GaN and p-GaN regrowth on the c -plane of the trench bottom are slow compared to the lateral regrowth on semipolar surfaces near the vertical sidewall, as can be inferred from Figure d,f. High-angle annular dark-field scanning transmission electron microscopy (STEM-HAADF) imaging was performed along a [101̅0] zone axis ( m -axis), revealing the interface between the c -plane-terminated GaN and the SiO 2 mask.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…The starting regrowth interface is slightly displaced from the initial trench edge due to mass transport via sublimation and condensation of Ga during temperature ramp-up and annealing (Figure e). , The terminal growth surface was observed in cross-section by cleaving along a [12̅10] axis ( a -axis), exposing the (101̅0) ( m -plane) surface (Figure f). The UID-GaN and p-GaN regrowth on the c -plane of the trench bottom are slow compared to the lateral regrowth on semipolar surfaces near the vertical sidewall, as can be inferred from Figure d,f. High-angle annular dark-field scanning transmission electron microscopy (STEM-HAADF) imaging was performed along a [101̅0] zone axis ( m -axis), revealing the interface between the c -plane-terminated GaN and the SiO 2 mask.…”
Section: Resultsmentioning
confidence: 71%
“…For simplicity, the following results and discussion concern trenches along the m -axis. Recent publications of regrowth on mesa structures also reported a faster growth rate near mesa edges than the trench center due to preferential diffusion of Ga adatoms from the mask to mesa edge and favorable Ga adsorption on {11̅01} facets . The lower acceptor concentration near the mesa edge was attributed to lower Mg doping efficiency. , …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Implant- and diffusion-based selective-area doping (SAD) methods have been actively investigated, and each faces its respective challenges. Selective-area etching of GaN followed by regrowth or selective-area growth is intuitively straightforward but has been hampered by the damage and contamination incurred during conventional inductively coupled plasma (ICP) etching. In the context of etch-and-regrowth, several groups have developed processes to mitigate or repair ICP etching damage with promising results. Recently, we reported an alternative, in situ etching of GaN with the use of tertiarybutylchloride (TBCl), a Cl-based organometallic precursor. Initial findings indicated that the TBCl etching of GaN has a sufficiently high etch rate and produces minimal damage or contamination. , This etching technique, however, has yet to be tested in working GaN electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…[35] and [36], the method of GaN secondary growth to fabricate the proposed CS-SJ HEMT is given below. First, metal organic chemical vapor deposition (MOCVD) was used to deposit an Mg-doped [37], [38] p-type GaN pillar with a thickness of T epi and a concentration of N 3 on an n-type GaN substrate, which allows the fabrication of vertical p-n junctions with low-doped high-mobility drift layers. A trench with a length of 2L p and a thickness of T epi is formed in the middle by the chlorine-based inductively coupled plasma (ICP) dry etching recipe with a very low RF power, and the UV-chemical treatment was used to treat it before the regrowth process [36].…”
Section: Fabrication Processmentioning
confidence: 99%